Association Between Local Skin Reactions and Efficacy with 5-Fluorouracil 4% Cream in Actinic Keratosis: A Post-Hoc Analysis of Two Randomised Clinical Trials - Markus V. Heppt; Kilian Trin; Anne-Cécile Mille; Mélanie Groc; Alain Delarue; Nathalie Bégeault (Dermatology and Therapy)
Abstract Introduction Topical 5-fluorouracil (5-FU), 5% or 4% cream, is recommended among first-line treatments for actinic keratosis (AK). Local skin reactions (LSRs) are an expected and transient response to treatment with 5-FU but can lead to treatment discontinuation when severe. This analysis aimed to investigate whether the severity of LSRs during the treatment was associated with lesion clearance assessed 4 weeks after completing treatment. Methods This post hoc analysis pooled data from two randomised clinical trials (HD-FUP3B-048 and HD-FUP3B-049). Only patients treated with once-daily 5-FU 4% for 4 weeks were considered. Analyses included LSR severity at week 2 and 4 and clearance 4 weeks after completing treatment (week 8). Analysed LSRs were erythema, scaling, oedema, crusting, erosions, stinging and pruritus, which were each categorised as mild, moderate, severe or none. Response was categorised as complete clearance (CC; clearance of all lesions), partial clearance (PC; ≥ 75% clearance) or no clearance (NC; < 75% or for subgroup analyses NC < 100%). Results Data from 397 patients were included. The median number of AK was 11 (lower quartile Q1 = 7 and upper quartile Q3 = 18) and grades were mild to moderate (86.4% of patients) and severe. At week 8, 321 patients (80.9%) had CC/PC and 76 (19.1%) had NC. Patients who achieved CC/PC had, at baseline, more lesions, a more severe disease and lesions preferentially on the ears/face than patients with NC. In adjusted logistic regression analyses and across all LSR grades, CC/PC at week 8 was associated with occurrence of erythema, oedema, crusting and stinging at week 2 and all LSRs at week 4. Severe erythema observed at week 2 was significantly associated with lesion clearance compared with mild erythema. At week 4, both severe and moderate erythema, moderate scaling and moderate pruritus were significantly associated with lesion clearance at week 8 compared with mild LSRs. Results according to the LSR severity for patients who had 100% clearance are quite similar. Conclusion Our analysis showed that the severity of LSRs during 5-FU 4% treatment for AK was associated with a higher clearance rate. It appears that severe LSRs did not compromise treatment efficacy. Because LSRs can still be unpleasant, strategies must be developed to relieve patients to allow continued 5-FU 4% application.